2015
DOI: 10.5897/ajar2012.2179
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of air flow patterns in perfomance of flat plate solar collectors

Abstract: Solar drying is one of the promising methods of reducing post-harvest losses in rural areas. Studies have shown that, heat transfer mechanisms in a solar collector influences the performance of solar dryers. This study aims at improving heat transfer in flat plate solar collectors by designing different air flow patterns inside the collector. Three flat plate solar collectors were constructed by using Pterocarpus timber (Mninga) and tested for their effect in heat transfer at various flow patterns. Three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Ramadhani et al [22] present a study to improve the heat exchange in the solar drier, the authors carried out a comparative study between a flat air solar collector with a single passage, salary collector with double passage (flow parallel) and a solar collector with double passage (flow against current), the results show that the latter model gives better thermal efficiency. So, they noticed that the value of the efficiency of the double duct countercurrent sensor equals 38.2% i.e., an improvement of 8.3% compared to a single duct sensor, they concluded that the double duct counter-current sensor has a large exchange surface therefore an increase in the heat exchange between the absorber and the heat transfer fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Ramadhani et al [22] present a study to improve the heat exchange in the solar drier, the authors carried out a comparative study between a flat air solar collector with a single passage, salary collector with double passage (flow parallel) and a solar collector with double passage (flow against current), the results show that the latter model gives better thermal efficiency. So, they noticed that the value of the efficiency of the double duct countercurrent sensor equals 38.2% i.e., an improvement of 8.3% compared to a single duct sensor, they concluded that the double duct counter-current sensor has a large exchange surface therefore an increase in the heat exchange between the absorber and the heat transfer fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the glass cover are also important; thus, a high transmittance and low reflectance in the visible range and low absorbance and transmittance in the infrared range must characterize the glazing material. Generally, increasing the glass thickness or the number of glass sheets leads to the reduction of the transmittance [9]. The effects of the number of glass sheets and the glazing properties on the thermal performance of a solar collector were also considered in references [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%